Preparação e caracterização de dispersões coloidais de nanopartículas de prata testadas como aditivos fotocatalíticos - Caio Menna Barreto Hussene (2023)
At the present work, silver nanoparticles (Ag-nps) colloidal dispersions were produced by photoreduction synthesis. Different experiments were conducted varying reaction parameters such as exposure time to UVC light, volume and concentration of metal and polymer sources. The Ag-nps dispersions were characterized by UV-vis absorption spectroscopy, electron diffraction, transmissions and scanning electron microscopies. Titanium dioxide (TiO2), vastly used as pigment for acrylic paint for real state applications, presents photocatalytic activity. It can be enhanced by interacting with Ag-nps. Two paints were produced, one containing Ag-nps and another one without. Its decontamination activities were compared using methylene blue as standard contaminant. Silver nanoparticles containing paint presented better decontamination activity.